Buff: a collie, and other dog-stories. - Terhune, Albert Payson, 1872-1942. (New York, Grosset & Dunlap, 1961)
Buff helps clear his master's name of suspicion in a theft. Includes seven other stories of canine valor.
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Short stories